Influence of extremely low-frequency magnetic field on chemotherapy and electrochemotherapy efficacy in human Caco-2 colon cancer cells. (3rd April 2022) - Alkis, Mehmet Esref; Akdag, Mehmet Zulkuf; Kandemir, Sevgi Irtegun
ABSTRACT: Although chemotherapy (CT) has some adverse effects on healthy tissues and cells, it is widely preferred for treating patients with cancer. Drug resistance is one of the major impediments to successful cancer treatment. Electrochemotherapy (ECT) is a technique where cancer cells are rendered permeable to medications. Thanks to this permeability, the dose of the medication required for cancer treatment decreases. Our aim in this study is to examine the effects of short-term extremely low-frequency magnetic fields (ELF-MFs) on CT and ECT treatments in Caco-2 colon cancer cells. The Caco-2 cancer cells were treated with 5-fluorouracil (5-FU, 50 µM) and ECT (strength:1125 V/cm, duration:100 µs, frequency:1 Hz), alone as well as in combinations with ELF-MF (4 mT, 10 min). MTT assay was used to determine the efficacy of the treatments. Our findings in the study showed that ECT was much more successful than 5-FU treatment alone in Caco-2 colon cancer cells. Application of 4 mT ELF-MF after CT significantly increased the viability of the Caco-2 cancer cells compared to the CT group alone (p < .05). An increase in the viability of cells treated with 4 mT after ECT was observed compared to ECT alone. Similarly, there was an increase in the viability of cells treated with MF prior to ECT treatment (p < .05). The results show that exposure to ELF-MF at 4 mT flux density significantly reduces CT and ECT treatment efficacy in Caco-2 colon cancer cells.